A comprehensive comparison of circulating tumor cells and breast imaging modalities as screening tools for breast cancer in Chinese women - Shao, Xuan; Jin, Xiaoyan; Chen, Zhigang; Zhang, Zhigang; Chen, Wuzhen; Jiang, Jingxin; Wang, Zhen; Cui, Ying; Fan, Wan-Hung; Wang, Ke; Yu, Xiuyan; Huang, Jian (Frontiers in Oncology, 2022)
Background Circulating tumor cells (CTC) have been recognized as a sensitive biomarker for breast cancer (BC). This study aimed to comprehensively compare CTC with imaging modalities, including ultrasonography, mammography, and contrast-enhanced magnetic resonance imaging (MRI) in screening for BC in Chinese women. Methods Three hundred forty-three participants were enrolled in this study, including 102 treatment-naive BC patients, 177 with breast benign diseases (BBD) and 64 healthy females. All participants underwent CTC testing and at least one of the following examinations, ultrasonography, mammography, and MRI at the Second Affiliated Hospital of Zhejiang University between December 2017 and November 2020. CTC were quantitatively assessed using cell counting (CTC detection rate/counts) and categorially examined using a cutoff value (CTC classification). Diagnostic power of CTC tests and imaging modalities, including accuracy and capability to predict clinicopathological characteristics of BC, were evaluated and compared. Results CTC classification with a cutoff value of 2 showed a “good” diagnostic accuracy of 0.889 for early to mid-stage BC comparable to breast imaging modalities using Breast Imaging-Reporting and Data System (BI-RADS). MRI demonstrated the highest sensitivity of 0.872 for BC and CTC classification had the highest specificity of 0.938. A relatively low sensitivity was found for mammography in this cohort of patients. Successful detection of BC by CTC detection rate/counts, but not CTC classification, correlated with two important clinicopathological features, American Joint Committee on Cancer (AJCC) stage and tumor-node-metastasis (TNM) stage. Detection power of certain imaging modalities was also associated with AJCC stage (ultrasonography, P = 0.0438 and MRI, P = 0.0422) and lymph node metastasis (ultrasonography, 0.0157). There were clear correlations between CTC tests (counts or classification) and imaging BI-RADS scoring system in detecting positive BC cases (P < 0.05). Further correlation analysis suggested that CTC quantity, but not CTC classification, had the capability to predict clinicopathological traits of BC that were identified by ultrasonography. Conclusions CTC tests have a diagnostic potency comparable to breast imaging modalities, and may be used as an alternative screening tool for BC.